Prevalence of Helicobacter Pylori infection in patients with gastrointestinal symptoms in an urban area of ​​Lima, Peru, 2021 - Guevara-Tirado, Alberto (2022)
Helicobacter pylori infection has a high prevalence in Peru and in the world and is highly associated with gastrointestinal ulcer and gastric cancer. The objective of this research is to determine the prevalence of Helicobacter Pylori in an urban population that attends a medical consultation for the first time due to gastrointestinal symptoms. Descriptive, prospective, cross-sectional study carried out in a population of both sexes and all ages in the district of Villa el Salvador. A 74.3% prevalence of H. Pylori is considered, with a higher prevalence in the intermediate adult and older adult age groups (75%). Likewise, there was a greater attendance to medical consultation on the part of the female sex (n = 208). It is concluded that there is a high prevalence of Helicobacter Pylori infection in patients with gastrointestinal symptoms.